THE IMPACT OF TYROSINE KINASE INHIBITORS ON FATHERHOOD IN PATIENTS WITH CHRONIC MYELOID LEUKEMIA, A SINGLE INSTITUTION EXPERIENCE - Mohammad Abu-Tineh (Elsevier, 2021)
Objective: Following the launch of the TKI's (tyrosine kinase inhibitors) for the treatment of CML, establishing its significant control over the disease, other dimensions have emerged in regard to the safety of treatment, particularly the effect on Male fertility and fatherhood. This study was conducted to review the real-life data on the effect of TKI on the fertility of male patients in the National Center of cancer care and research (NCCCR) in Qatar. Case report: Inclusion Criteria: Male patient diagnosed with CML, in Chronic or accelerated phase; 18 years of age or older and actively receiving tyrosine kinase inhibitors including (Imatinib, dasatinib,nilotinib) with the following: -Patients with no known issues with regards to fertility, (fertility is intact) Patients who developed fertility issues after the diagnosis of CML and starting TKI's. has been evaluated by an andrologist, and his evaluation concluded its TKI related. Methodology: A single-center study conducted a mixed-design study by phone interviews with CML male patients in the Chronic or accelerated phase, being followed up in NCCCR (national center for cancer care and research), evaluating the effect of Imatinib, Dasatinib, nilotinib, on their fertility whether they are taking it as first, a second, or third line of treatment. Results: 150 patients were interviewed to be included in the study, 22 patients had concerns related to medications safety and possible transmission of the disease, 33 patients had their families completed by the time of diagnosis. 26 patients have met the inclusion criteria, offspring's total number was 43, 97.6% were full-term, had a normal delivery, and normal average weight at delivery. No stillbirths, fetal demise, or congenital anomaly were reported. All offspring had normal development and growth. Conclusion: Around 98% of male CML patients taking imatinib, Dasatinib, Nilotinib had their offspring born normally with no delivery complications noted, all had no congenital anomaly had normal growth and development, and no CML-related cancers were diagnosed. Further studies with a larger sample size are required to shed light on the TKI outcome on fatherhood in CML patients.